2017
DOI: 10.3390/s17081882
|View full text |Cite
|
Sign up to set email alerts
|

A Vision-Based Wayfinding System for Visually Impaired People Using Situation Awareness and Activity-Based Instructions

Abstract: A significant challenge faced by visually impaired people is ‘wayfinding’, which is the ability to find one’s way to a destination in an unfamiliar environment. This study develops a novel wayfinding system for smartphones that can automatically recognize the situation and scene objects in real time. Through analyzing streaming images, the proposed system first classifies the current situation of a user in terms of their location. Next, based on the current situation, only the necessary context objects are fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…A major focus on CV-based approach is how to make visual information more accessible through recognizing objects [73], obstacles [74], color-codes or landmark (e.g., storefronts [43]), or through processing of tags such as barcodes [75], QR codes [76], and RFID [77]. Extending this focus, researchers have proposed indoor positioning and navigation systems [78,47,79]. However, Saha et al [43] concluded that for a deployable level of accuracy, using CV techniques alone is not sufficient yet.…”
Section: Use Of Computer Vision In Navigation For People With Visual ...mentioning
confidence: 99%
“…A major focus on CV-based approach is how to make visual information more accessible through recognizing objects [73], obstacles [74], color-codes or landmark (e.g., storefronts [43]), or through processing of tags such as barcodes [75], QR codes [76], and RFID [77]. Extending this focus, researchers have proposed indoor positioning and navigation systems [78,47,79]. However, Saha et al [43] concluded that for a deployable level of accuracy, using CV techniques alone is not sufficient yet.…”
Section: Use Of Computer Vision In Navigation For People With Visual ...mentioning
confidence: 99%
“…These aids convey information to users via different modalities: auditory [1,15,29,82,86] and vibrotactile [4,52,69,74]. Audio aids provide information with either verbal warnings and instructions [3,19,58,88] or sonification [7,36,43,61] or both [45]. For example, NavCog3 used BLE beacons for localisation and provide turn-by-turn instructions and descriptions of nearby landmarks and points of interest via bone-conducting headphone [81].…”
Section: Technology-based Mobility Aidsmentioning
confidence: 99%
“…From a cognitive load perspective, it is not surprising that realtime route information notably increases the rate of success among participants who are visually impaired or blind (Ko and Kim, 2017;Bai et al, 2018;Balata et al, 2018;Giudice et al, 2019). When information is provided in real-time, inclusion of landmarkbased information (Balata et al, 2018), egocentric directions (Giudice et al, 2019), and tailored guidance are preferred by travelers with visual impairments.…”
Section: Technologies and Devices Evaluatedmentioning
confidence: 99%
“…A majority of the studies had preview or training time to learn the wayfinding technology. When technology is being used, additional time for training participants in use of the technology is required (Kalia et al, 2010;Ko and Kim, 2017). The interconnections between the person, the technology, the environment and the systemic support deserves additional attention.…”
Section: Interconnections Across Findingsmentioning
confidence: 99%